Implementation of Library 2.0 Application: Lesson Learnt from Indonesian Library and Librarian - Noor, M U (KnE Social Sciences, 2018)
Despite Web 2.0 application achieving impressive growth over the last decade, the application of Web 2.0 in library, which is known as Library 2.0 concept, has received less implication than Web 2.0, particularly in Indonesia Library. This article makes an attempt to show and analyze the implementation of Library 2.0 in Indonesia compared with Global implementation of Library 2.0, whilst scrutinizing the existing literature that covers the implementation of library 2.0 in Indonesia and globally. More specifically, this article examines the implementation of Library 2.0 from 2006 to 2016 and that why Indonesian library did not yet enjoy the full benefit of Library 2.0 as other regions or nations. It finds that although there were great opportunities from internet users in Indonesia, library Indonesia still struggled to take all the benefits from the implementation of library 2.0 in Indonesia. Keywords: Web 2.0, library 2.0, Indonesia, social media, library